THE IMPLEMENTATION OF GO FISH GAME IN IMPROVING STUDENTS’ VOCABULARY - Hanafi Wibowo; Umi Laila Syarifah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
English is very important, since English is one of international language for communication. Although English in Indonesia is a second language, in fact not all Indonesians use it well. It was determined by their mastery on vocabularies. Therefore, one of the creative efforts to create fun learning is by using a vocabulary game called Go Fish. It uses Flash Card media. This study aims to explore whether the Flash Card or Go Fish game media can improve student’s vocabulary or not. Experiment with Class Action Research (CAR) is used as the method of this study. The population of the study is fifth graders of Elementary School. This study uses 2 Cycles in which each cycle has 3 times. 2 material meetings or playing games and 1 meeting is a post test. In the first cycle the value of students is still below the KKM of the school, with an average of 62.5, while the English language standard of KKM School is 65. It is required to do the second cycle to achieve the KKM score of the school. And after doing the second cycle, the students' values ​​have reached the School KKM score with an average of 81.75. This means that there is a significant difference in the average value between the first and second cycles. Therefore, it shows that the media of Flash Card or Go Fish games can improve students' English vocabulary.